Type IV Pili in Thermophilic Bacteria: Mechanisms and Ecological Implications - Naoki A. Uemura; Daisuke Nakane (Biomolecules)
Type IV pili (T4P) machinery is critical for bacterial surface motility, protein secretion, and DNA uptake. This review highlights the ecological significance of T4P-dependent motility in Thermus thermophilus, a thermophilic bacterium isolated from hot springs. Unlike swimming motility, the T4P machinery enables bacteria to move over two-dimensional surfaces through repeated cycles of extension and retraction of pilus filaments. Notably, T. thermophilus exhibits upstream-directed migration under shear stress, known as rheotaxis, which appears to represent an adaptive strategy unique to thermophilic bacteria thriving in rapid water flows. Furthermore, T4P contributes to the capture of DNA and phages, indicating their multifunctionality in natural environments. Understanding the T4P dynamics provides insights into bacterial survival and evolution in extreme habitats.